Improving the realibility of zinc oxide surge arrester / Azrina Abd Aziz and Tapan K. Saha - Abd Aziz, Azrina; K. Saha, Tapan (2006)
Reliable surge arresters can avoid unnecessary costs associated with equipment damage and ineffective lightning protection techniques. The most recent advance in the arrester is the Zinc Oxide arrester. However, some of the arresters can be damaged during their operation. The major cause of failure of the arresters is the surface flashover. This study aim to examine the surface flashover effect on ZnO arresters and develop method to reduce its effect and enhance the performance of the arrester. The experiment was designed to study the surface flashover effects. The ZnO blocks supplied by manufacturers were tested under different environments during multipulse currents. The observed degradation was qualitatively explained in terms of physical changes on the blocks and their electrical characteristics. The study found that the environments surrounding the ZnO blocks had no impact on surface flashover. The major finding leads to the possible contribution of the quality of surface material coating in protecting the blocks from surface flashover.